PHYLOGENETIC RELATIONSHIPS OF EARLY-MIDDLE ORDOVICIAN OSTRACODS OF BALTOSCANDIA - Tinn O.; Meidla T. (My University, 2004)
Phylogenetic analysis of the Early and early Middle Ordovician (Tremadoc and Arenig) ostracod species of Baltoscandia suggests a polyphyletic origin for the suborder Beyrichiocopa. Binodicopes, leiocopes and eridostracans are excluded from the beyrichiocopide clade. An independent origin from the basal ostracods is suggested for the binodicopes and eridostracans. The palaeocopes form a strongly supported monophyletic clade. Within this suborder, the ctenonotellid and the tetradellid families together form a monophyletic clade. The tetradellids are paraphyletic, being a stem-group for the ctenonotellids. Nanopsis nanella, the earliest known ostracod from the Tremadoc, is a basal palaeocope. The early eridostracans Conchoprimitia and Incisua, with their uncomplicated carapace morphology, might be the most primitive ostracods.
Keywords: ostracods; Ordovician; Baltoscandia; phylogeny; taxonomy; Paleozoic::Ordovician; Палеозой::Ордовикская